IMPLEMENTASI SUPERVISI AKADEMIK - Yosepha, Sr. Tanti; Chiar, H.M; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractAcademic supervision is designed for helping and guiding teachers to improvethe learning system in the classroom. The purpose of this research is to obtainthe accurate information about the Implementation of Academic Supervision atSekolah Kristen Immanuel II Sungai Raya. A qualitative approach with adescriptive case study method is applied in the research. The research"™ssubjects consist of 4 supervisors and 4 teachers. The data collection techniquesin this study is interview, observation and documentation. After the data hasbeen collected, the validity of the data is checked by using credibility andconfirmability tests. The main finding are the planning, the implementationand the feedback. In the end, the planning, implementation and feedback ofacademic supervision have the procedures and techniques that are acordanceto the experts in the field of academic supervision. The implication is that thesupervisory team has a supervision guide to develop teachers' teaching abilitiesso students are more motivated in teaching learning process.Keywords: Academic Supervision, Supervisor, Teacher